Gender responsive breeding: Lessons from Zimbabwe - Nchanji, Eileen; Nyarai, Chisorochengwe; Tsekenedza, Shylet; Bruce, Mutari; Gutsa, Freeman; Sondayi, Lloyd; Lutomia, Cosmas Kweyu; Onyango, Patricia (2022)
Gender analysis can have two kinds of influence and impact in a research program, such as plant breeding. One is to change the final results of the program by increasing the program’s attention to gender equality and to ensuring its benefits accrue to women, as well as to men. A second is to change the research process, by informing and altering research priorities and the program’s strategy for achieving them so that the program becomes more gender-responsive. Frequently this second type of change is a precondition for the first. The purpose of these Case Studies is to illustrate the impact of gender analysis on research in a real-life breeding program with an analysis of learning about gender and change in the breeding process. Better understanding of how gender analysis has been used to catalyze change in how plant breeding research is conducted should help programs interested in becoming gender-responsive to make more effective use of gender analysis. This document provides a Guide to writing a Case based on real experience in a plant breeding program or project for use by case study authors.